PJMHS 2021
DOI: 10.53350/pjmhs211572062
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Irritable Bowel Syndrome (IBS) and its Risk Factors among MBBS Students of Allama Iqbal Medical College, Lahore

Abstract: Background: Currently, there is a growing concern towards epidemiological and clinical research on functional gastrointestinal disorders. Irritable Bowel Syndrome is defined as a functional gastrointestinal disorder characterized by abdominal discomfort, abdominal pain, and altered bowel movements. It is the most common gastrointestinal disorder. It can be diarrhea-predominant IBS, constipation-predominant IBS, and mixed type IBS. Objective: The objective of this study was to determine the frequency of IBS amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Research has reported a 33.2% prevalence for irritable bowel syndrome (IBS) which is the most common FGID in the country [ 9 ]. In college students, functional IBS had a prevalence of 15.5%, while stress, sleep disturbances, and a positive IBS family history were all found to be significantly related to the diagnosis [ 10 ]. Female respondents depicted more severe symptoms, while a higher percentage of male respondents used medications to relieve constipation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has reported a 33.2% prevalence for irritable bowel syndrome (IBS) which is the most common FGID in the country [ 9 ]. In college students, functional IBS had a prevalence of 15.5%, while stress, sleep disturbances, and a positive IBS family history were all found to be significantly related to the diagnosis [ 10 ]. Female respondents depicted more severe symptoms, while a higher percentage of male respondents used medications to relieve constipation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%